Growth hormone pretreatment in man blocks the response to growth hormone-releasing hormone; evidence for a direct effect of growth hormone. - Ross, R; Borges, F; Grossman, A; Smith, R; Ngahfoong, L; Rees, L; Savage, M; Besser, G (1987)
The effect of pretreatment with biosynthetic methionyl human GH (hGH) on the GH response to GHRH has been studied in normal subjects. Eight volunteers were given either 4 IU hGH or placebo s.c. 12-hourly for 72 h before a GHRH test, or a single s.c. dose of 4 IU hGH 12 h before a GHRH test. Somatomedin-C (Sm-C) levels at the time of the GHRH tests were significantly elevated after treatment with hGH compared to placebo, and the GH response to GHRH was significantly attenuated. A further six subjects were given 2 IU hGH or placebo i.v., and i.v. GHRH 3 h later; there was no rise in Sm-C for the 5 h of the study after either treatment; nevertheless, the response to GHRH was completely abolished by pretreatment with hGH. These results demonstrate that GH can regulate its own secretion independently of changes in Sm-C levels, through a mechanism other than the inhibition of GHRH release. The attenuated response to GHRH in the presence of elevated Sm-C levels may be related to Sm-C, or be a more direct effect of the recently elevated GH levels.